X-Ray Reflectivity Study of Reactive DC Sputter Deposited Al2O3 Thin Films - A. Bender; E. Schippel (Active and Passive Electronic Components)
X-ray reflection was performed on Al2O3 thin films obtained by dc magnetron sputtering of aluminium in an argon/oxygen atmosphere. Two kind of films (amorphous and γ-Al2O3) were deposited on polished silicon wafers by conventional sputtering and sputtering with ion bombardment on the growing film. The x-ray reflection allows one to determine the surface roughness, mass density and thickness. The thickness was compared with ellipsometry data, and mechanical scanning measurements (stylus method). Transmission electron diffraction investigations were made for phase determination.